Effect of a yoga intervention on hypertensive diabetic patients - Shantakumari, Nisha; Sequeira, Sheifa; Eldeeb, Rasha (Journal of Advances in Internal Medicine, 2012)
Background - The concept of psychosomatic medicine has gained popularity, with yoga racing ahead in the field. The present study was conducted to assess the effectiveness of yoga as an intervention in the management of patients with Type 2 diabetes mellitus complicated with hypertension. Method - This study was carried out in 2005 in Medical College Trivandrum, Kerala, India among 100 hypertensive Type 2 diabetics. They were randomized into control and yoga groups. The yoga group practiced yoga daily for one hour and given oral hypoglycemic drugs for 3 months. The control group did not perform yogic exercises but given oral hypoglycemic drugs. Comparisons were drawn between systolic blood pressure (SBP), diastolic blood pressure (DBP), Fasting blood sugar (FBS) and post prandial blood sugar (PPBS) in both the groups at the start and at the end of 3 months. Paired and unpaired t tests were performed. Results - After intervention with yoga for 3 months the study group showed a significant decrease in SBP from 141.71±9.79 to 132.23±7.89 mm Hg, DBP from 90.57±4.07 to 85.49±5.03 mm Hg and FBS from 155.86±60.53 to 126.63±40.59 mg%. The reduction in PPBS from 240.31±79.42 to 208.74±73.05 mg% was however not proved to be significant statistically. Conclusion - These findings suggest that diabetics may benefit from yoga’s ability to improve the disease status. DOI: http://dx.doi.org/10.3126/jaim.v1i2.6526 Journal of Advances in Internal Medicine 2012;01(02):60-3.